Effect of carbon and oxygen on the high-temperature properties of silicon carbide–hafnium carbide nanocomposite fiber. Issue 4 (April 2023) - Bae, Seong-Gun; Kim, Sanghun; Jeong, Handeul; Lee, Yoonjoo; Jeong, Yeong-Geun; Shin, Dong-Geun
Abstract: The polymer-derived ceramics (PDCs) technique enables relatively low-temperature fabrication of Si-based ceramics, with silicon carbide fiber as a representative product. Polycarbosilane (PCS) has Si-C backbone structures and can be converted to silicon carbide. In the PDCs method, residual or excess carbon is generated from the precursor (C/Si ratio = 2 for polycarbosilane). Because of the non-stoichiometry of SiC, the physicochemical properties of polymer-derived SiC are inferior to those of conventional monolithic SiC. Herein, a silicon carbide-hafnium carbide nanocomposite fiber was optimized by crosslinking oxygen into the PCS fiber by regulating the oxidation curing time. During pyrolysis, carbothermal reduction, and sintering, carbon was removed by reaction with hydrogen and cross-linked oxygen. Non-destructive techniques (X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, and high-temperature thermomechanical analysis) were used to investigate the effects of excess carbon. The microstructure of the near-stoichiometric SiC-HfC nanocomposite fiber was more densified, with superior high-temperature properties.